2017
DOI: 10.1186/s12936-017-1790-3
|View full text |Cite
|
Sign up to set email alerts
|

Perceptions of malaria control and prevention in an era of climate change: a cross-sectional survey among CDC staff in China

Abstract: BackgroundThough there was the significant decrease in the incidence of malaria in central and southwest China during the 1980s and 1990s, there has been a re-emergence of malaria since 2000.MethodsA cross-sectional survey was conducted amongst the staff of eleven Centers for Disease Control and Prevention (CDC) in China to gauge their perceptions regarding the impacts of climate change on malaria transmission and its control and prevention. Descriptive analysis was performed to study CDC staff’s knowledge, at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1
1

Relationship

2
8

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 22 publications
0
4
0
1
Order By: Relevance
“…The impacts of extreme heat on population health in Australia are well documented [ 3 , 4 , 5 , 6 , 7 ]. With hot summers, SA is no stranger to prolonged periods of hot weather that have resulted in reported increases in morbidity and mortality in recent years [ 4 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…The impacts of extreme heat on population health in Australia are well documented [ 3 , 4 , 5 , 6 , 7 ]. With hot summers, SA is no stranger to prolonged periods of hot weather that have resulted in reported increases in morbidity and mortality in recent years [ 4 , 8 , 9 ].…”
Section: Introductionmentioning
confidence: 99%
“…shown in a study undertaken among CDC staff who agreed that climate change has negative consequences on health services [39]. Previous studies have indeed shown climate change to in uence malaria within this region with hotspots that are variable and include the high altitude areas [3].…”
Section: Perception Of Climate Change and Diseasesmentioning
confidence: 99%
“…akan dapat meningkatkan kemungkinan terjadinya kembali Kejadian Luar Biasa (KLB) Malaria mengingat malaria merupakan penyakit yang diklasifikasikan sebagai re-emerging disease. 7,8,9 Kabupaten pangandaran masih berpotensi besar kembali menjadi daerah endemis, karena selain ditemukan penderita positif juga masih ditemukan vektornya di beberapa tempat. 10 Kabupaten Pangandaran merupakan salah satu daerah tujuan wisata di Propinsi Jawa Barat.…”
Section: Pendahuluanunclassified